Ferroelectric Polymer Nanofibers Reminiscent of Morphotropic Phase Boundary Behavior for Improved Piezoelectric Energy Harvesting. Issue 15 (20th February 2022) - Park, Jiseul; Lim, Yeong‐won; Cho, Sam Yeon; Byun, Myunghwan; Park, Kwi‐Il; Lee, Han Eol; Bu, Sang Don; Lee, Ki‐Tae; Wang, Qing; Jeong, Chang Kyu
Abstract: Ferroelectric and piezoelectric polymers have attracted great attention from many research and engineering fields due to its mechanical robustness and flexibility as well as cost‐effectiveness and easy processibility. Nevertheless, the electrical performance of piezoelectric polymers is very hard to reach that of piezoelectric ceramics basically and physically, even in the case of the representative ferroelectric polymer, poly(vinylidene fluoride‐ co ‐trifluoroethylene) (P(VDF‐TrFE)). Very recently, the concept for the morphotropic phase boundary (MPB), which has been exclusive in the field of high‐performance piezoelectric ceramics, has been surprisingly confirmed in P(VDF‐TrFE) piezoelectric copolymers by the groups. This study demonstrates the exceptional behaviors reminiscent of MPB and relaxor ferroelectrics in the feature of widely utilized electrospun P(VDF‐TrFE) nanofibers. Consequently, an energy harvesting device that exceeds the performance limitation of the existing P(VDF‐TrFE) materials is developed. Even the unpoled MPB‐based P(VDF‐TrFE) nanofibers show higher output than the electrically poled normal P(VDF‐TrFE) nanofibers. This study is the first step toward the manufacture of a new generation of piezoelectric polymers with practical applications. Abstract : A new behavior of ferroelectric polymer reminiscent of morphotropic phase boundary (MPB) is demonstrated in P(VDF‐TrFE) according to copolymeric compositions. It is the surprising characteristics of electroactive polymers mimicking that of electroceramics. In the electrospun P(VDF‐TrFE) nanofibers, the 50/50 P(VDF‐TrFE) device induces the critical phase competition for MPB, resulting in much better performance than that of the 70/30 P(VDF‐TrFE) energy device.